A Systematic Literature Review of Implementation of Javanese Culture-Based Guidance and Counseling Services: An Effort to Foster Cultural Well-being in Indonesia - Ulya Makhmudah; Eza Sakti Daningrum; Novita Yuliana; Mulyaningtyas (Universitas PGRI Yogyakarta, 2025)
Globalization changes society into a modern lifestyle. An unprepared mindset leads Indonesian society to overlook its local culture. Thus, it requires effort to foster cultural well-being in Indonesia. Cultural wellbeing in this research includes the freedom to express history, heritage, and cultural traditions within the realm of guidance and counseling. Javanese culture is featured in this research because it is a rich culture in Indonesia, possessing excellent philosophical values. This research aims to analyze the references concerning the implementation of Javanese culture-based guidance and counseling services. The Javanese method applied was a Systematic literature review based on Kitchenham with 26 references. The research findings indicated that the implementation of Javanese culture-based guidance and counseling services was urgently needed to enhance cultural well-being in Indonesia. Javanese culture-based guidance and counseling characteristics include the use of teachings poured in manuscripts and tembang macapat, which can be implemented to develop counseling, group guidance, and to improve counselor personality competence. Keywords: guidance and counselling, javanese culture, cultural well-being